Economics of Cashew Nut Processing in Ondo State, Nigeria; Evidence from Jof Ideal Family Farms Limited - Idowu Oladeji Ojo (ZBW – Leibniz Information Centre for Economics, 2020)
Purpose: This paper examines the economics of cashew nut processing in Ondo state using JOF Ideal Family Farms Limited, Owo as a case study. It specifically examined the socio-economic characteristics of the workers of the company, the by-products derived from cashew nuts processing and the costs and returns associated with cashew nut processing and the major constraints associated with the processing of cashew nuts in the company. Research design, data and methodology: Purposive sampling was used to select JOF Ideal Family Farms Limited, Owo as the case study being the only cashew nut processing company in the state. Descriptive statistics such as mean, mode, median, frequency distribution, the use of tables etc. were employed to know the socio-economic characteristics of workers of the company, the byproducts derived from processed cashew nuts and the problems associated with cashew nut processing. The cost and returns of the cashew nut processing were determined using the Gross margin analysis. Results: Findings revealed that 16.7% of the workers were within ages 21 and 30 years while 83.3% of them were between 31 and 40 years. 11.1% of the workers are skilled while 88.9% of them are unskilled. The Gross margin analysis showed that the company cashew nut processing is profitable with Margin of ₦ 29,192,000 and ₦ 60,870,000 in year 2011 and 2012 respectively. Conclusion: Based on findings from the study, Cashew nut processing is profitable in the study area. In spite of the fact that cashew nut processing has numerous potentials to create employment, especially for women, its level of production is still low. To mention few, the study recommended that more farmers especially the youths should engage in cashew farming, this will increase the availability of cashew nuts for the processing industries. Government should provide adequate mechanization and incentive to reduce drudgery of cashew nut processing in the state.
Keywords: 330; Cashew nut; JOF; Economics; Ondo state; processing